In-Vitro and In-Vivo Hepatoprotective activity of Abutilon indicum L., Alangium salvifolium and Broussonetia papyrifera L. Silver Nanoparticles (International Journal of Food and Nutritional Sciences, 2022)
The ethanol extract of Abutilon indicumL., Alangium salvifolium and Broussonetia papyriferaL. Silver Nanoparticles (AgNPs) was tested for hepatoprotective activity against paracetamol- convinced hepatotoxicities in rats. AAbutilon indicumL., Alangium salvifolium and Broussonetia papyriferaL. AgNPs displayed significant hepatoprotective activity by reducing paracetamol- convinced change inbiochemical parameters that was apparent by enzymatic examination. The factory extract may intrude with free-revolutionary conformation, which may conclude in hepatoprotective action.